PENDEKATAN KEADILAN RESTORATIF: UPAYA MELIBATKAN PARTISIPASI KORBAN DAN PELAKU SECARA LANGSUNG DALAM PENYELESAIAN PERKARA PIDANA - Meliala, Nefa Claudia (Veritas et Justitia, 2015)
AbstractFrom our understanding of ius poenale and ius puniendi, crime logically is simply considered as any offense directed against the state. In other words, conflict between offender and the State. It follow that justice is related to number of cases processed and punishment served. From this perspective, the criminal justice system disregards victims’ and offenders’s needs for closure and personal justice.  The restorative justice system offers an alternate approach which may compensate the shortcomings of the existing criminal justice system that is by opening up the possibility of victims and offenders participation.